APPROBATION OF MICROBIALLY AVAILABLE PHOSPHORUS (MAP) DETERMINATION METHOD BY FLOW CYTOMETRY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Phosphorus (P) is among the most important nutrients required for bacterial growth. It has a great influence on microbial activity even at very small concentrations. Existing chemical methods are not able to determine P at low enough concentrations and to quantify biologically available phosphorus fractions. Therefore, a method of microbially available phosphorus (MAP) determination is used to quantify the amount of P at concentrations below 20 µg/l. Additionally, this method determines the amount of P that can be directly used by microorganisms.Originally it was determined by inoculating sample by Pseudomonas fluorescens (now Ps. brenneri) P17 strain and spread-plated on R2A agar for enumeration. Further, a more rapid method was developed by replacing heterotrophic plate count (HPC) by flow cytometry (FCM).In this paper the use of FCM for MAP determination is validated and compared with HPC method. The results of calibration are presented. The original pure P17 strain was used as inoculum and standards with different PO4-P concentrations were inoculated at 30°C. The gained yield factor by FCM was 1.59x108. FCM results showed strong correlation (R2=0.99) with HPC results, as pure culture was used. Therefore, flow cytometry is a rapid alternative to heterotrophic plate count method for microbially available phosphorus determination.